2018
DOI: 10.1002/ajmg.a.40492
|View full text |Cite
|
Sign up to set email alerts
|

A previously unrecognized 22q13.2 microdeletion syndrome that encompasses TCF20 and TNFRSF13C

Abstract: Phelan-McDermid syndrome (PMS, OMIM 606232) is a heterozygous contiguous gene microdeletion syndrome occurring at the distal region of chromosome 22q13. This deletion encompasses the SHANK3 gene at 22q13.33, which is thought to be the critical gene for the neurodevelopmental features seen in this syndrome. PMS is typically characterized by intellectual disability, autism spectrum disorder, absent to severely delayed speech, neonatal hypotonia, and dysmorphic features. Two patients presenting with classic clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…The reduction of cell cycle exiting leads to a reduction in neuronal output and these reasons cause small brain size, which is similar to a previous report of insm1 knockout mice . Besides, there are several reports showed that some patients with TCF20 mutations have microcephaly, which is constant to our mouse model . We further performed RNA‐seq to explore the possible target of TCF20.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The reduction of cell cycle exiting leads to a reduction in neuronal output and these reasons cause small brain size, which is similar to a previous report of insm1 knockout mice . Besides, there are several reports showed that some patients with TCF20 mutations have microcephaly, which is constant to our mouse model . We further performed RNA‐seq to explore the possible target of TCF20.…”
Section: Discussionsupporting
confidence: 86%
“…TCF20 was also found to play a role as transcriptional coactivator in modulating the transcriptional activity of Sp1, c-Jun, Est1, and RNF4 [18][19][20]. TCF20 is located in the chromosome 22q13.2 region, which is close to the Phelan-McDermid syndrome (PMS) candidate gene shank3 [21]. PMS, known as 22q13.3 deletion syndrome, involves a range of phenotypes, including global developmental delay, intellectual disability, neonatal hypotonia, autism, and autistic-like behaviors, which has caused PMS to be considered a syndromic form of ASD [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, TCF20 was one of the highest ranking candidate autism risk genes (category 2) according to the most recent version of the SFARI Gene resource. Mutations in TCF20 were also implicated in Phelan-McDermid syndrome ( Upadia et al, 2018 ), developmental disorders ( Deciphering Developmental Disorders Study, 2017 ), and schizophrenia ( Smeland et al, 2017 ). FBXO11 was prioritized as a strong ASD candidate gene ( Ji et al, 2016 ), and was recently reported to be associated with a variable neurodevelopmental disorder ( Gregor et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, TCF20 was one of the highest ranking candidate autism risk genes (category 2) according to the most recent version of the SFARI Gene resource. Mutations in TCF20 were also implicated in Phelan-McDermid syndrome (40), developmental disorders (41), and schizophrenia (42). Our ranking system also successfully predicted another ASD gene FBXO11 (ranked sixth).…”
Section: Discussionmentioning
confidence: 99%